ANALISIS OPTIMALISASI PROSES PERENCANAAN PENGELOLAAN ASET DAERAH DI PEMERINTAH KOTA SALATIGA - Wahyuningrum,, Endah; Larasati, Endang; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Asset or property is one of the potential areas to increase revenue so it can reduce dependence on subsidies from the central government. Therefore, local governments demanded to managing local asset in a professional, transparent, accountable, efficient, and effective. The planning process in asset management have more than the other management functions. Good planning is needed in the management assets to avoid waste in asset management related to a field that is wide enough, so need to think carefully about alternatives for decisions about the limited resources ownership.The reasearch used a descriptive qualitative method that lovated on the Departement of Revenue, Finance and Regional Assets. and focus on Process Optimization Analysis of Regional Asset Management Planning in the City of Salatiga. There were two data sources such primary and secondary. Its instruments used as research instrument, interview guide, and informant. The way how to determine its technique that applied purpisive sampling while collecting data using interview, observation, and library reasearch to get the whole data. Afterwards this analysis technicques using of qualitative data, with stage writing memos, coding, categorizing, display, and archive analytical.There were three phenomena which observed on this study, that is optimization of the regional asset management, asset management planning process, and indicators of asset management planning process optimization. From the research, that the optimization of the regional asset management is nor optimal, views of not compliance aspects in the implementation of regional wealth nmanagement. In the planning process has not running well because the stage not in accordance with the time schedule specified in the Standard Operating Procedure. Whereas, the indicator optimization of regional asset management planning process has not been in accordance with principle of legal certainty, the principle of accountability and principle of value.